The environment: A vector of phenotypic disparity during the settlement phase of coral reef fishes - Reynaud, Mathieu; Gairin, Emma; Lecchini, David; Laudet, Vincent; Frédérich, Bruno (Journal of experimental marine biology and ecology, 2023)
In coral reef fish, the transition from pelagic larvae to reef-associated juveniles is a complete metamorphosis in which coordinated physiological, morphological, and behavioural changes occur, enabling the fish to settle and grow in coastal habitats and then recruit into the adult population. Environmental factors can modulate different aspects of metamorphosis such as the timing of its initiation, its duration, and the coordination of the morphological changes. Here, we raised the coral-reef-dwelling convict surgeonfish, Acanthurus triostegus, in different types of habitats during the post-settlement period. The selected habitats, whether natural (beach rock, mangrove, and sand beach habitats where A. triostegus settle naturally), or experimental (pelagic ocean and oxygen depleted ‘dead’ zone) were characterized by their substrate type, fish community composition, and physico-chemical profile. By using landmark-based geometric morphometric methods, we compared growth, body shape changes, and quantified phenotypic disparity levels among and within the different habitats. The results showed that fish raised in mangrove grew faster than in the other habitats and, most importantly that different habitats lead to variations in the rate and the nature of shape transformation. The ontogenetic trajectories defined in the shape space differed across habitats in terms of length and direction. A peak of shape disparity was observed for the natural habitats at three days post settlement when compared to fish reared in dead zone or oceanic environment. Overall, these results suggest that environmental diversity could generate developmental plasticity, ultimately producing phenotypic disparity that may allow the acclimation of fish to their local environment. •Different settlement habitats induce variation in growth, body shape, and ontogenetic trajectory in a coral reef fish.•Different levels of phenotypic disparity within populations could be induced by the environment.•Metamorphosis is modulated by the environment.